2021
DOI: 10.1002/app.51677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crystallinity in carbon fiber‐reinforced poly(ether ether ketone) by using infrared low frequency Raman spectroscopy

Abstract: The degree of crystallinity of poly(ether ether ketone) (PEEK) in carbon fiber reinforced composites were evaluated by using infrared low frequency Raman spectroscopy. Reference PEEK samples with varying crystallinity which are evaluated using wide-angle X-ray diffraction (WAXRD) were prepared. These samples were used to create a calibration curve for crystallinity using low frequency Raman spectroscopy. The WAXRD and low frequency Raman methods directly correlated. Carbon fiber reinforced PEEK samples with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Before presenting computational analysis, the experimental findings are reviewed briefly. The experimental data have been reported previously [7] but here we newly processed the data in a form suitable for comparison with the computational results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Before presenting computational analysis, the experimental findings are reviewed briefly. The experimental data have been reported previously [7] but here we newly processed the data in a form suitable for comparison with the computational results.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular modes are expected to be more sensitive to the crystallinity, because the intermolecular distances and angles and chain alignment in polymers will be affected by the crystallinity. A team including some of the present authors has reported the use of a low-frequency Raman signal to evaluate the crystallinity of PEEK [7]. Although they found that the intensity of a Raman signal changed during crystallization as explained in the next section, the mechanism has not been elucidated.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations